2020
DOI: 10.35772/ghm.2020.01024
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features after emergency declaration in Hokkaido and report of 15 cases of COVID-19 including 3 cases requiring mechanical ventilation

Abstract: The ongoing spread of coronavirus disease (COVID-19) is a worldwide crisis. Hokkaido Prefecture in Japan promptly declared a state of emergency following the rapid increase of COVID-19 cases, and the policy became an example to mitigate the spread of COVID-19. We herein report 15 cases of COVID-19 including 3 cases requiring mechanical ventilation. Based on review of our cases, among patients over 50 years of age with underlying diseases such as hypertension and diabetes mellitus, and those who required oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Therefore, WHO guidance proposed that systemic corticosteroids should be carefully used only in selected cases. In addition, some recent Japanese studies have reported that ciclesonide, as one type of ICS, may have positive effects in treating COVID-19 [ 21 , 22 ]. However, this study concludes that recent usage of asthma medication did not affect clinical outcomes of COVID-19, independently.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, WHO guidance proposed that systemic corticosteroids should be carefully used only in selected cases. In addition, some recent Japanese studies have reported that ciclesonide, as one type of ICS, may have positive effects in treating COVID-19 [ 21 , 22 ]. However, this study concludes that recent usage of asthma medication did not affect clinical outcomes of COVID-19, independently.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the number of reported cases has continued to increase and Hokkaido has become the most heavily impacted area in Japan. Taking the situation very seriously, the Hokkaido Government issued a "Declaration of State of Emergency in Hokkaido" on February 28, 2020 [4]. With a decrease in the number of reported cases, Hokkaido's declaration of a state of emergency was then lifted on March 19.…”
Section: Introductionmentioning
confidence: 99%
“…1 The Japanese public health agencies found clustering in the “Three Cs”: closed spaces with poor ventilation, crowded spaces with many people, and close contact 2 ; however, the clinical investigation of Japanese patients with COVID‐19 is limited. 3 , 4 , 5 , 6 , 7 Besides, no study has existed evaluating COVID‐19 in outpatient settings although understanding COVID‐19 is crucial for frontline clinical practitioners. We aimed to describe and compare the demographic, clinical, and epidemiological characteristics and outcomes of patients with and without COVID‐19 who presented to the Teine Keijinkai Medical Center Infection Triage Clinic, Sapporo, Japan.…”
Section: Introductionmentioning
confidence: 99%